Obese with higher FNDC5/irisin levels have a better metabolic profile, lower lipopolysaccharide levels and type 2 diabetes risk - Bonfante, Ivan Luiz Padilha; Chacon-Mikahil, Mara Patricia Traina; Brunelli, Diego Trevisan; Gáspari, Arthur Fernandes; Duft, Renata Garbellini; Oliveira, Alexandre Gabarra [UNESP]; Araujo, Tiago Gomes; Saad, Mario Jose Abdalla; Cavaglieri, Cláudia Regina (Archives of Endocrinology and Metabolism, 2017)
Objective: Thus, the aim of this study was to compare if higher or smaller fibronectin type 3 domain-containing protein 5 (FNDC5)/irisin levels are associated with inflammatory and metabolic markers, caloric/macronutrient intake, physical fitness and type 2 diabetes mellitus (T2DM) risk in obese middle-aged men, and also to correlate all variables analyzed with FNDC5/irisin. Subjects and methods: On the basis of a cluster study, middle-aged obese men (IMC: 31.01 ± 1.64 kg/m²) were divided into groups of higher and smaller levels of FNDC5/irisin. The levels of leptin, resistin, adiponectin, tumor necrosis factor alpha (TNFα), interleukin 6 and 10 (IL6, IL10), lipopolysaccharide (LPS), glucose, insulin, glycated hemoglobin, insulin resistance and sensibility, lipid profile, risk of T2DM development, body composition, rest energy expenditure, caloric/macronutrient intake and physical fitness were measured. Results: The higher FNDC5/ irisin group presented improved insulin sensibility (homeostasis model assessment – sensibility (HOMA-S) (p = 0.01) and QUICKI index (p < 0.01)), insulin (p = 0.02) and triglyceride levels (p = 0.01), lower insulin resistance (homeostasis model assessment – insulin resistance (HOMA-IR) (p = 0.01), triglycerides/glucose (TYG index) (p = 0.02), neck circumference (p = 0.02), risk of T2DM development (p = 0.02), tendency to decrease serum resistin (p = 0.08) and significant lower LPS levels (p = 0.02). Inverse correlations between FNDC5/irisin and body weight (r -0.46, p = 0.04), neck circumference (r -0.51, p = 0.02), free fat mass (r -0.49, p = 0.02), triglycerides (r -0.43, p = 0.05) and risk of developing T2DM (r -0.61, p = 0.04) were observed. Conclusions: These results suggest that higher FNDC5/irisin levels in obese middle-aged men are related to a better metabolic profile and lower risk of T2DM development and serum LPS, a potential inducer of insulin resistance.
Keywords: Irisin; Lipopolysaccharide; Metabolism; Obese; Type 2 diabetes